Effects of delaying demands on noncompliance and escape‐maintained problem behavior. (4th May 2018) - Bloom, Sarah E.; Clark, Daniel R.; Boyle, Megan A.; Clay, Casey J.
Abstract : A recommendation for caregivers of individuals who engage in noncompliance (i.e., any behavior other than compliance) and escape‐maintained problem behavior is to provide a choice for when to complete a nonpreferred task. Although this may immediately abate problem behavior, it is unclear whether problem behavior and noncompliance are just as likely to occur when the task is re‐presented. Therefore, the purpose of this study was to determine the extent to which allowing participants (3 children with developmental disabilities) to delay a nonpreferred task decreased problem behavior and/or increased compliance when that task was re‐presented and to determine whether the effectiveness of such an intervention could be augmented by the addition of escape extinction. Results showed that when delayed tasks were re‐presented, participants emitted more problem behavior than when those tasks were unavoidable from the outset and, further, that participants continued to engage in noncompliance with tasks despite the ability to delay them. Including escape extinction resulted in a decrease in problem behavior and an increase in compliance for all participants.